Endophytic non-pathogenic Fusarium oxysporum reorganizes the cell wall in flax seedlings - Wojtasik, Wioleta; Dymińska, Lucyna; Hanuza, Jerzy; Burgberger, Marta; Boba, Aleksandra; Szopa, Jan; Kulma, Anna; Mierziak, Justyna (Frontiers in Plant Science, 2024)
Introduction Flax (Linum usitatissimum) is a crop producing valuable products like seeds and fiber. However, its cultivation faces challenges from environmental stress factors and significant yield losses due to fungal infections. The major threat is Fusarium oxysporum f.sp lini, causing fusarium wilt of flax. Interestingly, within the Fusarium family, there are non-pathogenic strains known as biocontrols, which protect plants from infections caused by pathogenic strains. When exposed to a non-pathogenic strain, flax exhibits defense responses similar to those seen during pathogenic infections. This sensitization process activates immune reactions, preparing the plant to better combat potential pathogenic strains. The plant cell wall is crucial for defending against pathogens. It serves as the primary barrier, blocking pathogen entry into plant cells Methods The aim of the study was to investigate the effects of treating flax with a non-pathogenic Fusarium oxysporum strain, focusing on cell wall remodeling. The infection’s progress was monitored by determining the fungal DNA content and microscopic observation. The plant defense response was confirmed by an increase in the level of Pathogenesis-Related (PR) genes transcripts. The reorganization of flax cell wall during non-pathogenic Fusarium oxysporum strain infection was examined using Infrared spectroscopy (IR), determination of cell wall polymer content, and analysis of mRNA level of genes involved in their metabolism. Results and discussion IR analysis revealed reduced cellulose content in flax seedlings after treatment with Fo47 and that the cellulose chains were shorter and more loosely bound. Hemicellulose content was also reduced but only after 12h and 36h. The total pectin content remained unchanged, while the relative share of simple sugars and uronic acids in the pectin fractions changed over time. In addition, a dynamic change in the level of methylesterification of carboxyl groups of pectin was observed in flax seedlings treated with Fo47 compared to untreated seedlings. The increase in lignin content was observed only 48 hours after the treatment with non-pathogenic Fusarium oxysporum. Analysis of mRNA levels of cell wall polymer metabolism genes showed significant changes over time in all analyzed genes. In conclusion, the research suggests that the rearrangement of the cell wall is likely one of the mechanisms behind flax sensitization by the non-pathogenic Fusarium oxysporum strain. Understanding these processes could help in developing strategies to enhance flax’s resistance to fusarium wilt and improve its overall yield and quality.